Water filter application with zeolit composite material in laying hens farm towards the egg quality - M. Fauzi; I. I. Arief; Z. - Abidin (Journal of the Indonesian Tropical Animal Agriculture, 2023)
This study aimed to analyze the physical, chemical, and microbiological properties of applying an antibacterial water filter made from zeolite composites in laying hens. This study used a completely randomized design with a factorial pattern with 2 factors and 3 replications for egg quality. Factor A is the zeolite treatment, and factor B is the day of egg collection after being filtered. If the measures show a significant difference, it is continued with the least significant difference test, and the chemical quali-ty of the eggs and the microbiology of the eggs are tested using the t-test analysis (paired samples). The results showed that there was a significant interaction between the zeolite treatment and the day after the filter was installed after the eggs were collected. This increases the value of egg length, egg width, shell weight, shell thickness, and haugh units. Furthermore, the chemical quality of eggs treated with zeolite alone on day 3 had a significant effect (P<0.05) on the dry matter and egg fat content . The microbiological quality of the eggs also showed that the zeolite treatment reduced the TPC value and effectively killed Escherichia coli and Salmonella sp. It was concluded that the application of zeolite filters to the drinking water of laying hens could improve physical quality, maintain chemical quality, and is effective as an antibacterial against bacterial populations, Escherichia coli and Salmonella sp bacteria in eggs.